Early repolarization pattern as a predictor of atrial fibrillation recurrence following radiofrequency pulmonary vein isolation. Issue 4 (19th January 2019) - Hunuk, Burak; de Asmundis, Carlo; Mugnai, Giacomo; Velagic, Vedran; Ströker, Erwin; Moran, Darragh; Ruggiero, Diego; Hacioglu, Ebru; Umbrain, Vincent; Verborgh, Christian; Beckers, Stefan; Poelaert, Jan; et al.
Abstract: Background: Early repolarization patterns (ERP) have been found to be associated with poor cardiovascular end points. We aimed to evaluate the ERP prevalence among patients with structurally normal hearts undergoing radiofrequency (RF) pulmonary vein isolation (PVI) for paroxysmal atrial fibrillation (AF) ablation and its association with the AF recurrence. Methods: All consecutive patients who underwent RF‐PVI as index procedure for paroxysmal AF in our center were evaluated. Exclusion criteria: structural heart disease, ongoing use of Class I/III antiarrhythmics, complete‐bundle‐branch‐block. Lateral (I, aVL, V5 –V6 ), inferior (II, III, aVF), or infero‐lateral (both) ERP were defined in baseline ECG as horizontal/downsloping J‐point elevation ≥1 mm in two consecutive leads with QRS slurring/notching. Documented episodes of AF lasting ≥30 s were considered recurrence. Results: Of 701 cases, 434 patients (305 males, 58 ± 11 years) were included for analysis. ERP observed in 67 patients (15.4%) (Infero‐lateral n  = 26, inferior n  = 23, lateral n  = 18) which were significantly younger, demonstrating longer PR‐interval and lower heart rates. At a mean follow‐up of 22.1 ± 9.7 months, AF recurrences were found in 107 patients (24.6%). In middle‐aged patients (≥40–<60 years; n  = 206, 79% male), those with an infero‐lateral ERP had higher recurrence compared with the ones without (56.3% vs. 19%; p  = 0.002). Infero‐lateral ERP was significantly predicting recurrence (HR 2.42, 95% CI 1.21–4.82; p  = 0.01). Conclusion: Early repolarization patterns was more prevalent in our AF population than in the general population. Infero‐lateral ERP in baseline ECG might predict AF recurrence in the follow‐up after RF‐PVI in middle‐aged patients.